2010
DOI: 10.1128/jvi.00229-10
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Uncoating of Intact Enveloped Viruses

Abstract: Experiments in the 1960s showed that Sendai virus, a paramyxovirus, fused its membrane with the host plasma membrane. After membrane fusion, the virus spontaneously "uncoated" with diffusion of the viral membrane proteins into the host plasma membrane and a merging of the host and viral membranes. This led to deposit of the viral ribonucleoprotein (RNP) and interior proteins in the cell cytoplasm. Later work showed that the common procedure then used to grow Sendai virus produced damaged, pleomorphic virions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…This method is supported by experiments that have shown that SV is capable of infection at low temperatures that do not allow endocytosis or membrane fusion to occur (51). Direct observation by electron microscopy also provides evidence that virus penetration occurs at the cell surface via formation of a pore (15,41).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This method is supported by experiments that have shown that SV is capable of infection at low temperatures that do not allow endocytosis or membrane fusion to occur (51). Direct observation by electron microscopy also provides evidence that virus penetration occurs at the cell surface via formation of a pore (15,41).…”
supporting
confidence: 55%
“…An alternate method of entry is that SV attaches to the cell surface receptor and directly injects its RNA by forming a pore in the cell membrane (15,41). The nucleocapsid core is responsible for maintaining the rigid structure of the virus (9), so after release of the genome the virus is no longer stable and can be released from the cell surface (41), leaving the pore in the membrane temporarily intact (28,31).…”
mentioning
confidence: 99%
“…However, this process is very similar in many aspects to the entry mechanism proposed for nonenveloped viruses such as poliovirus (39) and also suggested to occur with Sendai virus (18). Previous studies have observed a rapid and highly efficient RNA release for poliovirus, which also occurs in an endocytosis-independent manner but is dependent on temperature, actin cytoskeleton, and tyrosine kinases (40).…”
Section: Discussionmentioning
confidence: 88%
“…It is significant that in the process of infection by arboviruses the viral membranes remain outside the cell. If the virus membrane disengages from the host cell membrane instead of merging with it, then not only would the cell not have viral proteins on its surface but also the release of the virus membrane pieces with embedded proteins could serve as immunologic decoys (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation